Right ventricular evaluation to improve survival outcome in patients with severe functional mitral regurgitation and advanced heart failure undergoing MitraClip therapy. (15th November 2016) - Giannini, Cristina; Fiorelli, Francesca; Colombo, Antonio; De Carlo, Marco; Weisz, Sara Hana; Agricola, Eustachio; Godino, Cosmo; Castriota, Fausto; Golino, Paolo; Petronio, Anna Sonia
Abstract: Background: Percutaneous mitral valve repair (PMVR) is a new option for high risk patients with functional mitral regurgitation (FMR) and severely depressed left ventricular (LV) function who are not responding to optimal medical therapy. However patients with end stage heart failure have a high mortality rate despite MitraClip implantation. We sought to identify right ventricular (RV) echocardiographic predictors of outcome in a large cohort of patients with severe FMR and advanced heart failure in order to select the most appropriate candidate who could benefit from this treatment. Methods: 169 consecutive high surgical risk patients affected by severe FMR underwent PMVR with the MitraClip System. The primary end-point was cardiovascular mortality at the longest available follow-up. Results: The survival free from cardiac death was 97.6% at 30 days, 86.7% at 1 year, 71.5% at 2 years and 61.6% at 3 years. Patients who died were significantly older and had more severe comorbidities and signs of more advance heart failure. Independent predictors of cardiovascular mortality were severely impaired renal function [glomerular filtration rate (GFR) < 30 ml/min; OR = 5.46, 95%CI = 1.43–20.84, ( p = 0.01)] and RV systolic dysfunction [peak systolic velocity tissue Doppler imaging (PSVtdi ) < 9.5 cm/s; OR = 0.57, 95%CI = 0.39–0.82, ( p = 0.003)]. Conclusion: Our study shows the importance of RV systolic function evaluation for the risk stratification of patients with FMR and advanced heart failure undergoing PMVR. Severe right ventricular failure identifies patients with an increased risk for cardiovascular mortality despite MitraClip treatment. RV PSVtdi is the best independent predictor of outcome in these end-stage patients for a threshold value of 9.5 cm/s.